Efficacy of individualized homeopathy as an adjunct to standard of care of COVID-19: A randomized, single-blind, placebo-controlled study. (August 2022) - Nayak, Debadatta; Gupta, Juhi; Chaudhary, Anupriya; Singh, Krishna Gopal; Deshmukh, Abhijeet; Das, Deblina; Saha, Abhishek; Kumar, Deepak; Kumar, Ashwini; Goenka, Ajay; Mishra, S.K.; Gupta, Sanjay; et al.
Highlights: A randomized, placebo-controlled trial of adjunct homeopathy with standard of care for COVID-19 was conducted on 300 patients. Primary outcome on total symptom score measured over 10 days decreased significantly favoring Standard of care + Homeopathy. Recovery was earlier in Standard of care + Homeopathy group by 02 days showing the added benefits of homeopathy. Resolution of fever was 20 h earlier in Standard of care + Homeopathy. Arsenicum album, Bryonia alba and Phosphorus were the most frequently prescribed medicines.